Exploring the Shariah-Compliant Hotel Market: Meeting the Needs of Muslim Travelers - Singgalen, Yerik Afrianto (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2024)
This study explores the dynamics of guest preferences and satisfaction within the context of Sharia-compliant hospitality, using data from 445 verified reviews at The Sahira Hotel. Employing a descriptive-analytic methodology, the research utilizes visitor data extracted from Agoda’s review platform, focusing on room preferences, stay duration, and satisfaction ratings. The dataset was systematically filtered, cleaned, and categorized to ensure relevance and accuracy before conducting qualitative and quantitative analyses. Key findings reveal significant trends in visitor demographics and preferences. Families with young children and teenagers strongly preferred spacious accommodations, particularly the Family Deluxe Triple, accounting for over 35% of such bookings. In contrast, solo travelers, representing 20% of the dataset, favored functional and affordable options like the Deluxe Twin. Ratings analysis revealed the Deluxe Twin as the most highly rated room type, receiving over 40% "Exceptional" ratings. Short stays dominated the data, with 60% of guests staying for one night, emphasizing the importance of high-quality service for transient visitors. The study also underscores the significance of cultural and religious considerations, such as Halal-certified amenities and gender-sensitive spaces, in enhancing guest satisfaction. By aligning operational strategies with these insights, the findings provide actionable recommendations for optimizing marketing efforts, improving service delivery, and ensuring consistent guest satisfaction. This research contributes to the broader discourse on integrating cultural sensitivity with modern hospitality practices, offering a pathway for sustainable growth in the competitive halal tourism market.